ANIMATED TAPE DISPENSER - KUEHN, THOMAS P; MONNIER, VAN HONG TRAN; ABEL, STACY L (2012)
A tape dispenser includes a housing having an outer surface and is configured to contain a roll of adhesive tape. Coupled to the outer surface of the housing includes features of an animal including at least one animal leg coupled to the housing and extending outwardly from the outer surface of the housing. The at least one animal leg moves relative to and along the outer surface of the housing upon adhesive tape being dispensed from the roll of adhesive tape.